FEMININITY, MASCULINITY, PATRIARCHAL DOMINATION: REPRESENTATION OF GENDER RELATIONS IN TELEVISION DRAMA “FROM FIVE TO NINE”: FEMINITAS, MASKULINITAS, DOMINASI PATRIARKI: REPRESENTASI RELASI GENDER DALAM DRAMA TELEVISI “FROM FIVE TO NINE” - Raihan Rizqi Aghniyaa; Rouli Esther Pasaribu2 (LLDIKTI Wilayah X, 2023)
This study aims to determine the form of representation of gender relations in the television drama series “From Five to Nine” (2015) and the meanings as well as critics to be conveyed through the drama. The theory used in this study is R.W. Connell’s theory of gender and hegemonic masculinity (1985, 1987), Rosemarie Tong’s liberal feminism theory (2014), and Stuart Hall’s representation theory (1997). The research method used in this research is semiotic analysis using John Fiske’s semiotic theory of television codes (2001) which divides film analysis into three levels: reality, representation, and ideology. The research focusses on the main female and male characters, Sakuraba Junko and Hoshikawa Takane. The analysis includes characterization, dialogue, conflict, camera shots, music, editing, and ideological values ​​contained in each scene segment. Based on the analysis that has been done, the researcher finds that there is a change in the form of the relationship that occurres between Junko and Takane from the beginning of the episode to the end. At the beginning of their relationship, Takane is described as more dominant than Junko, but Junko, as an independent female character, does not want to be dominated, so their relationship changes in a more equal direction. This drama also represents a relationship of interdependence and not a power relationship between the two characters.